Problematika Hukum dalam Penetapan Ganti Rugi Pembebasan Lahan - Talib, Solihin H.; Talib, Riski; Moonti, Roy Marthen (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The determination of compensation in the process of land acquisition for infrastructure development in Indonesia still faces various complex legal problems. Although has been regulated in Law Number 2 Year 2012, its implementation often creates inequality, both in terms of compensation value and procedures for community involvement. The phrase “decent and fair” in the regulation opens wide room for interpretation, so there is often a mismatch between the value set by the government and the expectations of the community. This imbalance is exacerbated by weak public participation, lack of legal literacy, and the dominance of legal-formalistic approaches. Agrarian conflicts, legal uncertainty, and disregard for the social and cultural values of indigenous peoples also exacerbate the situation. Therefore, policy reforms based on a participatory approach, institutional strengthening, and the use of digital technology to realize transparency and accountability are needed. Fair compensation must ensure protection of citizens' human rights and build trust in the legal system in the development process.